171 Preclinical studies support therapeutic application of the leukemic cell-based cancer relapse vaccine DCP-001 in ovarian cancer. (10th December 2020) - Nagasawa, Maho; Bos, Remco; Zuo, Haoxiao; Wang Yin, Kiave Yune Ho; Lierop, Marie-José van; Tabruyn, Sebastien; Manting, Erik; Bruyn, Marco de; Nijman, Hans; Singh, Satwinder KAur; Singh, Satwinder Kaur
Abstract : Background: Ovarian cancer (OC) is the gynecological malignancy with the highest mortality due to the late diagnosis of disease and a high rate of relapse following initial therapy. Immunotherapy in combination with standard treatment modalities has emerged as an encouraging treatment approach to surmount this unmet medical need. DCP-001 is a cancer relapse vaccine derived from the DCOne human leukemic cell line and is currently progressing through clinical trials in hematological malignancies. During manufacturing, DCOne cells are shifted towards a mature dendritic cell phenotype, rendering the cells highly immunogenic and providing the basis for DCP-001, which is administered as an intradermal vaccine. DCOne cells express multiple common tumor associated antigens (TAA) such as WT-1, RHAMM, PRAME and MUC-1, which have been documented as potential target antigens in ovarian cancer. This observation suggests that DCP-001 vaccination may also have an anti-tumor effect in OC. To support this hypothesis, we assessed the capacity of DCP-001 to induce immune responses against OC in human peripheral blood mononuclear cells (PBMCs) and a humanized mouse model for OC. Methods: The effect of DCP-001 on T cells from OC patients or healthy donors was evaluated after a 3 week culture of peripheral blood mononuclear cells (PBMCs) with or without DCP-001. Cytotoxic activity was analysed by specific IFNg production and CD107a expression when these cells were subsequently cultured with the OC cell line SKOV3. The effect of DCP-001 vaccination in vivo was evaluated in humanised NCG mouse subcutaneously engrafted with SKOV3 OC cells. Mice received intra-peritoneal (i.p.) vaccination with DCP-001 either after or prior to SKOV3 engraftment and tumor size was measured to evaluate the efficacy of DCP-001. Results: In vitro, DCP-001 was shown to activate both CD4+ as well as CD8+ T cells and to induce formation of memory T cells. Importantly, DCP-001-stimulated CD8+ T cells from OC patients were shown to exert a HLA class I dependent, cytotoxic immune response to OC cells. In vivo, in an ovarian tumor mouse model, significant reduction of tumor growth rate and partial or even complete tumor regressions were observed in mice vaccinated with DCP-001, particularly when administered as relapse vaccine (prior to tumor engraftment), as compared to PBS treated mice. Conclusions: These pre-clinical in vitro and in vivo results support the potential use of DCP-001 as a cancer relapse vaccine in ovarian cancer, with the aim to reduce disease recurrence following initial standard of care therapy.